Exploring the relationship between economic activity, population, and energy consumption on environmental degradation in 10 OIC Countries - Zuhri, Saifudin; Adrian, Muhammad Adi; Nisa, Nadhifah An (Indonesian Journal of Islamic Economics Research, 2025)
Environmental degradation is a manifestation of ecosystem damage caused by unsustainable activities, one of which is reflected in increased carbon emissions. This study aims to analyze the relationship between economic activities and environmental degradation in 10 member countries of the Organization of Islamic Cooperation (OIC) using quantitative data from 2008 to 2022. The Panel VECM method was used to identify long-term and short-term relationships between variables. The estimation results indicate that, in the long term, population, electricity consumption, economic growth, FDI, and renewable energy consumption have a significant impact on carbon emissions. Conversely, total energy consumption and the HDI are not significant. These findings encourage the government to shift from fossil fuel use to new and renewable energy and minimize the conversion of green areas into residential areas. Additionally, fossil fuel use must be balanced with investments in new and renewable energy to control rising carbon emissions alongside economic activities.